Infinite dimensional VARs and factor models - Alexander Chudik; Mohammad Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper introduces a novel approach for dealing with the 'curse of dimensionality' in the case of large linear dynamic systems. Restrictions on the coefficients of an unrestricted VAR are proposed that are binding only in a limit as the number of endogenous variables tends to infinity. It is shown that under such restrictions, an infinite-dimensional VAR (or IVAR) can be arbitrarily well characterized by a large number of finite-dimensional models in the spirit of the global VAR model proposed in Pesaran et al. (JBES, 2004). The paper also considers IVAR models with dominant individual units and shows that this will lead to a dynamic factor model with the dominant unit acting as the factor. The problems of estimation and inference in a stationary IVAR with unknown number of unobserved common factors are also investigated. A cross section augmented least squares estimator is proposed and its asymptotic distribution is derived. Satisfactory small sample properties are documented by Monte Carlo experiments. An empirical application to modelling of real GDP growth and investment-output ratios provides an illustration of the proposed approach. Considerable heterogeneities across countries and significant presence of dominant effects are found. The results also suggest that increase in investment as a share of GDP predict higher growth rate of GDP per capita for non-negligible fraction of countries and vice versa.
Keywords: C10; C33; C51; O40; 330; large N and T panels; weak and strong cross section dependence; VAR; global VAR; factor models; capital accumulation and growth; VAR-Modell; Faktorenanalyse; Monte-Carlo-Methode; Investition; Wirtschaftswachstum; Theorie; Schätzung; Welt